PEMBINAAN PEMBELAJARAN BAHASA INGGRIS DALAM MENINGKATKAN KOSAKATA MELALUI FUN ENGLISH LEARNING - Hijrahyanti, Hesti; Harmilawati, Harmilawati; Purnama, Atmaranie Dewi (Universitas Sanata Dharma, 2023)
This community service program aims to introduce English vocabulary learning among early childhood or children in the Kindergarten/TPA of Balle Village. The teaching method used in this activity is through the Fun English Learning method, which means teaching English to children who have a fun English learning concept. It includes learning activities using songs and games. The results of this program show that the participants have started to have fun learning English and that students' vocabulary and understanding of English vocabulary have increased compared to the beginning of the meeting. Even though there are still mistakes, they have started to be confident and don't feel ashamed.